Unconfirmed presence of the territorial golden jackal Canis aureus and grey wolf Canis lupus groups in the Poljanska Sora river valley and Škofjeloško hribovje hills in July 2020 - Rudi Kraševec; Aleksander Trajbarič; Špela Hočevar; Monika Možina; Urša Fležar (Natura Sloveniae)
n/a